Implementation Of Risk Management In Management Of Waqf Assets - Faisal Faisal (International Journal Reglement & Society (IJRS), 2021)
The understanding and empowerment of waqf property among Muslims has undergone significant changes. From time to time, the understanding of productive waqf is increasingly developing and comprehensive which aims to develop the economy, for the social benefit of the community. Therefore, Muslims have found a new economic face that emerged from waqf, namely by establishing foundations or economic development institutions oriented to community service. This shows how important it is to empower productive waqf assets to improve the people's economy. The wider understanding and empowerment of waqf assets is very important, especially if it is associated with the concept of developing productive waqf in improving the people's economy. The procedure used to collect data in this study is in the form of documentation, namely guidelines used in the form of notes or quotes, legal literature searches, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. In fact, most of the currently established social institutions are funded by waqf and are engaged in productive waqf management in order to provide guidance and protection to the community, such as orphanages, child protection institutions, educational institutions, health institutions, distribution of clean water throughout the world. city and various other social activities. The role of waqf managers is also getting wider, not only maintaining and doing routine things, but also looking for new innovations in order to develop and empower these waqf assets. For this reason, there needs to be improvement efforts aimed at fixing waqf management and eliminating the causes of the deterioration of waqf management due to nazhir's actions and negligence, through the application of risk management.